Retention of pro-vitamin A carotenoid in composite bread baked with high quality cassava flour from yellow-fleshed cassava root - Awoyale, W.; Abass, A.; Maziya-Dixon, Busie (Functional Food Center, 2018)
Background: As one of the most widely consumed foods, bread is one of the most important agricultural products. Bread made from high-quality cassava flour is consumed in some parts of Sub-Sahara Africa (SSA). The bread has no pro-vitamin S carotenoids (pVAC) due to the use of artificial colorants. Consequently, there is a need for the use of pVAC rich foods for bread production. Foods that are rich with pro-vitamin A carotenoids can be converted into retinol in the human body and whose bioconversion contributes to the reduction of vitamin A deficiency diseases (VAD). VAD has caused annual loss of life in SSA, especially in Nigeria. The yellow-fleshed cassava root might contribute to the reduction of this disease. The high quality yellow cassava flour (YHQCF) produced from yellow-fleshed cassava root may contribute to the pVAC composition of bread. As a result, there is a need for the evaluation of the retention of pVAC in composite bread baked with high quality cassava flour from yellow-fleshed cassava roots. Methods: The YHQCF was produced from TMS01/1368 cassava variety. The bread loaves consisted of 20% and 100% YHQCF and were produced by mixing the sugar, margarine, yeast, improver, and salt with the composite flour and YHQCF respectively, after which water was added and mixed to get the homogenous dough. The dough was proofed for 2.5 hours, kneaded, cut into shape, placed in a lubricated baking pan, and baked at 200oC for 30 min. Analyses of the pro-vitamin A (cis and trans-β carotene) and dry matter content were carried out on all the samples, including samples from the YHQCF production steps using standard methods. The samples from the YHQCF production steps were chosen and analyzed for pVAC in order to check the levels of degradation of the pVAC from the raw cassava root to using the root for flour production and the quantity of pVAC retained when 100% of the YHQCF is used for bread production compared to 20% composite. The β-carotene nutrient retention of the bread was also calculated. Results: The results demonstrated how the total pVAC content of the raw yellow-fleshed cassava root was 16.83 µg/g dry basis with 29% dry matter (DM) content. Subsequent processing by peeling, washing, grating, and dewatering into granules (56% DM) caused 48% reduction in the pVAC content which was reduced to 40% after drying and milling the dried grits into YHQCF (97% DM). Preparation of recipe for bread demonstrated how the 20% composite flour dough (61% DM) contained 0.29 µg/g db pVAC representing 1.72% retention, which was later reduced to 0.25 µg/g db pVAC or 1.49% retention after baking (62%DM). On the other hand, bread loaves baked from 100% YHQCF (67% DM) retained 0.74 µg/g db pVAC representing 4.40% of the 16.83 µg/g db pVAC in the starting raw material. Conclusions: The bread produced from 100% YHQCF may contribute to the pro-vitamin A status of bread consumers in SSA more than the 20% YHQCF composite. However, both bread samples are low in pVAC. In order to attain the required retinol equivalent level after bioconversion in the human body, consumption of other foods rich in vitamin A would be required to attain the required retinol equivalent level after bioconversion in the human body but can be enhanced if consumed with other foods rich in vitamin A.